Multiple forms of long-term synaptic plasticity at hippocampal mossy fiber synapses onto interneurons - Galván, Emilio J. (2010)
The hippocampal mossy fiber (MF) pathway originates from the dentate gyrus granule cells and provides a powerful excitatory synaptic drive to neurons in the dentate gyrus hilus and area CA3. Much of the early work on the MF pathway focused on its electrophysiological properties, and ability to drive CA3 pyramidal cell activity. Over the last ten years, however, a new focus on the synaptic interaction between granule cells with inhibitory interneurons has emerged. These data have revealed an immense heterogeneity of long-term plasticity at MF synapses on various interneuron targets. Interestingly, these studies also indicate that the mechanisms of MF long-term plasticity in some interneuron subtypes may be more similar to pyramidal cells than previously appreciated. In this review, we first define the synapse types at each of the interneuron targets based on the receptors present. We then describe the different forms of long-term plasticity observed, and the mechanisms underlying each form as they are currently understood. Finally we highlight various open questions surrounding MF long-term plasticity in interneurons, focusing specifically on the induction and maintenance of LTP, and what the functional impact of persistent changes in efficacy at MF – interneuron synapses might be on the emergent properties of the inhibitory network dynamics in area CA3.